2001
DOI: 10.1177/107906320101300203
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Factors Related to Deviant Sexual Arousal Among Juvenile Sex Offenders

Abstract: Abstract:To date, there has been limited literature on the measurement of sexual arousal in adolescent sex offenders. The data that exist have been somewhat mixed in terms of factors related to deviant sexual arousal in this group. The present study, with 71 adolescent sex offenders, investigates the relationship between offender and offense characteristics, including gender of victim, history of sexual abuse, history of physical abuse, race, and interactions between these factors in the prediction of physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 18 publications
6
38
1
1
Order By: Relevance
“…Of course, it is also possible that there are variables besides those examined in the present study that uniquely contribute to one type of sexual offending or another. In the future, controlled studies should examine variables (e.g., deviant sexual beliefs and arousal patterns; Lakey, 1992;Murphy, DiLillo, Haynes, & Steere, 2001) pertaining to putative specific causes of sexual offending in youths.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, it is also possible that there are variables besides those examined in the present study that uniquely contribute to one type of sexual offending or another. In the future, controlled studies should examine variables (e.g., deviant sexual beliefs and arousal patterns; Lakey, 1992;Murphy, DiLillo, Haynes, & Steere, 2001) pertaining to putative specific causes of sexual offending in youths.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these rates vary by study method. For example, studies of youth in residential facilities (Hunter et al, 2003) reveal higher rates of sexual victimization (75%) than studies of youth in community settings (39%; e.g., Murphy, DiLillo, Haynes, & Steere, 2001). Authors of a meta-analysis of more than 50 studies (N > 9,000 youth) reported that the average rate of sexual abuse may be as low as 40% (Burton & Schatz, 2003).…”
Section: Sexual Victimization Of Adolescent Sexual Abusersmentioning
confidence: 95%
“…Race, although not widely investigated, might be an important characteristic, since several authors have suggested that Caucasian sex offenders show different sexual arousal patterns compared with sex offenders from ethnic minorities (Murphy et al, 2001;Långström, 2004). While many studies have demonstrated low (verbal) IQ in delinquent youth (Loeber and Farrington, 1998;Vermeiren et al, 2002a), this does not appear to distinguish sex offenders and non-sex offenders (e.g.…”
Section: Introductionmentioning
confidence: 96%